A clinical audit of thallium-technetium subtraction parathyroid scans. Issue 776 (June 1990) - Samanta, A.; Wilson, B.; Iqbal, J.; Burden, A. C.; Walls, J.; Cosgriff, P.
Abstract : Eighty six consecutive thallium-technetium subtraction parathyroid scans performed over a three year period for hypercalcaemia have been evaluated. Twelve had chronic renal failure, 11 had hypercalcaemia due to non-hyperparathyroid causes and in 10 the imaging study was technically inadequate. The remaining 53 technically adequate studies performed for hypercalcaemia clinically thought to be possibly due to hyperparathyroidism have been analysed. Of 20 (38%) positive scans, 13 came to surgery (10 correctly localized parathyroid adenomas, 2 with multiple gland hyperplasia, and 1 papillary carcinoma of the thyroid). Of 33 (62%) negative scans, 9 had surgical exploration on the basis of strong clinical grounds and all had parathyroid adenomas. Multiple biochemical parameters have been assessed in relation to a positive outcome on scan. The adjusted calcium-phosphate product and the ratio of the adjusted calcium-phosphate product to creatinine (Ca x P/Cr) were both significantly lower in the scan positive group (P less than 0.01). The scan positive group had a significantly higher mean level of PTH (P less than 0.001) and lower mean level of phosphate (P less than 0.001). The present experience shows that parathyroid imaging is useful in localizing parathyroid adenomas in 50% of cases (10 out of 19). This figure is at the lower end of the range of previously published results. It is less effective in demonstrating multiple gland hyperplasia. The decision as to whether to undertake surgical exploration when the scan is negative has been based successfully on clinical judgement. We feel that an analysis of this nature is important, as it gives insights into the practical relevance of parathyroid imaging in the context of routine clinical work.